Post-COVID-19 condition: a sex-based analysis of clinical and laboratory trends - Delfino, Carlos; Poli, M. Cecilia; Vial, Cecilia; Vial, Pablo A.; Martínez, Gonzalo; Riviotta, Amy; Arbat, Catalina; Mac-Guire, Nicole; Hoppe, Josefina; Carvajal, Cristóbal; Muñoz Venturelli, Paula (Frontiers in Medicine, 2024)
Background and aim: Post-COVID-19 condition (PCC) encompasses long-lasting symptoms in individuals with COVID-19 and is estimated to affect between 31-67% of patients, with women being more commonly affected. No definitive biomarkers have emerged in the acute stage that can help predict the onset of PCC, therefore we aimed at describing sexdisaggregated data of PCC patients from a local cohort and explore potential acute predictors of PCC and neurologic PCC.June 2020 and July 2021 were registered, and clinical and laboratory data was recorded. Only those <65 years, discharged alive and followed up at 6 and 12 months after admission were considered in these analyses. Multivariate logistic regression analysis was performed to explore variables associated with PCC (STATA v 18.0).From 130 patients in the cohort, 104 were contacted: 30% were women, median age of 42 years. At 6 months, 71 (68%) reported PCC symptoms. Women exhibited a higher prevalence of any PCC symptom (87 vs 60%, p=0.007), lower ferritin (p=0.001) and procalcitonin (p=0.021) and higher TNF levels (p=0.042) in the acute phase compared to men.Being women was independently associated to 7.60 (95% CI 1.27-45.18, p=0.026) higher risk for PCC. Moreover, women had lower return to normal activities 6 and 12 months.Our findings highlight the lasting impact of COVID-19, particularly in young women, emphasising the need for tailored post-COVID care. The lower ferritin levels in women are an intriguing observation, warranting further research. The study argues for comprehensive strategies that address sex-specific challenges in recovery from COVID-19.